Sputum as a source of adipokines in bronchial asthma - V. N. Mineev; T. M. Lalaeva; T. S. Vasiljeva; A. A. Kuzmina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
Forty-four patients with allergic (ABA) and non-allergic (NABA) variants of bronchial asthma (BA) were examined to evaluate levels of key adipokines (leptin, resistin, adiponectin) in sputum in different variants of BA. Adipokines in sputum and blood plasma were measured by Enzyme-Linked Immunosorbent Assay (ELISA). The indices that reflect the percentage of adipokines in sputum regarding adipokines in plasma of the same patients were worked out to evaluate the ratio of levels of corresponding adipokines in plasma and sputum in patients with BA. Two regularities are clearly seen in the study: the first - levels of proinflammatory adipokines (leptin, resistin) in sputum in ABA correlate directly with indicators of respiratory function but levels of anti-inflammatory adipokines (adiponectin) in sputum correlate inversely with indicators of respiratory function; the second -correlation of levels of the studied adipokines with indicators of respiratory function are almost not revealed in NABA. The first regularity reflects the important fact that the content of adipokines in bronchial secretion is to a certain extent one of regulating local mechanisms in target organ controlled system levels of corresponding adipokines in exacerbation of BA.